2023
DOI: 10.31004/obsesi.v7i1.3478
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Permainan Petak Umpet dalam Meningkatkan Kemampuan Matematika pada Anak Usia Dini

Abstract: Permainan petak umpet merupakan permainan tradisional Indonesia yang dapat digunakan untuk mengajarkan matematika pada anak usia dini. Penelitian ini bertujuan untuk  menganalisis permainan  petak umpet  dalam meningkatkan kemampuan matematika pada anak usia dini. Penelitian ini merupakan penelitian kualitatif. Subyek penelitian ini adalah anak usia dini yang berada di Kota Semarang, Bekasi, dan Pekalongan. Metode pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Then research (Cinthia et al, 2022) that playing hide and seek can improve children's gross motor skills with an initial average of 46.1 with a percentage of 22.2% then in cycle I it increases with an average score of 63.3 with a percentage of 55.6 % and in cycle II increased with an average value of 71.1 with a percentage of 77.8%. Furthermore, research (Ashar & Inrawulan, 2021) revealed that in cycle I it resulted in a percentage of 79% of children being able to walk, run and jump, resulting in 70% of children being able to move their eyes, legs and head, as well as physical games in following the rules resulting in 43%, so that the average is 64% and the success indicator reaches 80%, while in cycle II it produces a percentage of 82% of children can walk, run and jump, resulting in 83% of children being able to move their legs, eyes and head, as well as in physical games in following the rules produces 65%, so that the average in cycle II produces 82%, it has reached an indicator of success Furthermore, in the study (Agustin et al, 2016) explained that the influence of the traditional game of hide and seek on aspects of literacy (language) development gave a result of 59.1% on children's literacy. Then in the study (Qurani, 2020) explained that the hijaiyyah letter card hide-and-seek game method obtained percentage results in the first cycle observing teacher activity by 76.6%, in observing student activity cycle I by 70%, then in cycle II the observation of teacher activity was 91.6%, in the observation of student activity by 90% then there was an increase in students' ability to recognize hijaiyyah letters by using the hide and seek game with an average value of cycle I was 63.15 and the child's learning mastery presentation was 42.10% then in cycle II obtained an average value of 80.26 with a child's learning achievement of 89.47%.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Then research (Cinthia et al, 2022) that playing hide and seek can improve children's gross motor skills with an initial average of 46.1 with a percentage of 22.2% then in cycle I it increases with an average score of 63.3 with a percentage of 55.6 % and in cycle II increased with an average value of 71.1 with a percentage of 77.8%. Furthermore, research (Ashar & Inrawulan, 2021) revealed that in cycle I it resulted in a percentage of 79% of children being able to walk, run and jump, resulting in 70% of children being able to move their eyes, legs and head, as well as physical games in following the rules resulting in 43%, so that the average is 64% and the success indicator reaches 80%, while in cycle II it produces a percentage of 82% of children can walk, run and jump, resulting in 83% of children being able to move their legs, eyes and head, as well as in physical games in following the rules produces 65%, so that the average in cycle II produces 82%, it has reached an indicator of success Furthermore, in the study (Agustin et al, 2016) explained that the influence of the traditional game of hide and seek on aspects of literacy (language) development gave a result of 59.1% on children's literacy. Then in the study (Qurani, 2020) explained that the hijaiyyah letter card hide-and-seek game method obtained percentage results in the first cycle observing teacher activity by 76.6%, in observing student activity cycle I by 70%, then in cycle II the observation of teacher activity was 91.6%, in the observation of student activity by 90% then there was an increase in students' ability to recognize hijaiyyah letters by using the hide and seek game with an average value of cycle I was 63.15 and the child's learning mastery presentation was 42.10% then in cycle II obtained an average value of 80.26 with a child's learning achievement of 89.47%.…”
Section: Resultsmentioning
confidence: 67%
“…Then research (Sentaningrum, 2021) explains that children in the pre-cycle say the numbers 1-10 get an average value of 7 percentage points an average value of 70%, followed by cycle I get a value of 5 percentage points an average value of 50% and in cycle II obtained an average value of 8 percentages of 80% then in sorting the numbers 1-10 in the pre-cycle obtained an average value of 5 percentages of an average value of 50%, then in cycle I obtained an average value of 6 percentages of the average value 60%, and in cycle II obtained an average value of 9 percentage points an average value of 90%. Furthermore, research (Marini et al, 2023) explains that playing hide and seek can develop children's mathematical abilities because at the hompipah stage children are introduced to many concepts of many and few, choosing the next cat by lining up is associated with concepts in ordinal numbers and objects. Subsequent research (Muharrahman et al, 2023) explained that playing hide and seek can improve children's gross motor skills, namely at the time of initial observation the child's motor was 47.5 with a presentation of 18.2% then in cycle I there was an increase in the average value of 61.3 or of 45.5%, and in cycle II of 63.7% and the average value of 73.6.…”
Section: Resultsmentioning
confidence: 99%
“…Sehingga permainan petak umpet sering dijadikan alternatif dalam mengembangkan beberapa aspek perkembangan anak salah satunya ialah aspek perkembangan sosial emosional pada anak usia dini. Selain ramah dengan lingkungan permainan petak umpet ini juga dapat melatih kemampuan anak untuk beradaptasi dengan lingkungan secara teratur, karena anak akan mampu berpikir secara kritis dan mampu mengatur emosi saat bersembunyi ataupun mencari teman yang lawan mainnya serta anak juga mampu mengembangkan kemampuan sosial mereka seperti kerjasama tim dan berkomunikasi secara nonverbal (Muharrahman et al, 2023). Permainan petak umpet anak usia dini dapat bermanfaat bagi perkembangan anak di segala bidang; Salah satu area yang dapat dibina melalui kegiatan ini adalah perkembangan sosial-emosional anak.…”
unclassified